Pressure drop and arterial compliance – Two arterial parameters in one measurement. (4th January 2017) - Rotman, Oren M.; Zaretsky, Uri; Shitzer, Avraham; Einav, Shmuel
Abstract: Coronary artery pressure-drop and distensibility (compliance) are two major, seemingly unrelated, parameters in the cardiovascular clinical setting, which are indicative of coronary arteries patency and atherosclerosis severity. While pressure drop is related to flow, and therefore serves as a functional indicator of a stenosis severity, the arterial distensibility is indicative of the arterial stiffness, and hence the arterial wall composition. In the present study, we hypothesized that local pressure drops are dependent on the arterial distensibility, and hence can provide information on both indices. The clinical significance is that a single measurement of pressure drop could potentially provide both functional and bio-mechanical metrics of lesions, and thus assist in real-time decision making prior to stenting. The goal of the current study was to set the basis for understanding this relationship, and define the accuracy and sensitivity required from the pressure measurement system. The investigation was performed using numerical fluid–structure interaction (FSI) simulations, validated experimentally using our high accuracy differential pressure measurement system. Simplified silicone mock coronary arteries with zero to intermediate size stenoses were used, and various combinations of arterial distensibility, diameter, and flow rate were simulated. Results of hyperemic flow cases were also compared to fractional flow reserve (FFR). The results indicate the potential clinical superiority of a high accuracy pressure drop-based parameter over FFR, by: (i) being more lesion-specific, (ii) the possibility to circumvent the FFR dependency on pharmacologically-induced hyperemia, and, (iii) by providing both functional and biomechanical lesion-specific information.